Long‐term mortality in heart failure with mid‐range ejection fraction: systematic review and meta‐analysis. (31st August 2022) - Raja, Deep Chandh; Samarawickrema, Indira; Das, Souvik; Mehta, Abhinav; Tuan, Lukah; Jain, Sanjiv; Dixit, Sanjay; Marchlinski, Frank; Abhayaratna, Walter P.; Sanders, Prashanthan; Pathak, Rajeev K
Abstract: Aims: Heart failure patients with mid‐range ejection fraction (HFmrEF) have overlapping clinical features, compared with patients with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). We aim to perform a meta‐analysis of studies reporting long‐term outcomes in HFmrEF compared with HFrEF and HFpEF. Methods and results: Data from 18 eligible large‐scale studies including 126 239 patients were pooled. Patients with HFmrEF had a lower risk of all‐cause death than those with HFrEF [risk ratio (RR) = 0.92; 95% CI = 0.85–0.98; P < 0.001]. This significant difference was seen in the follow‐up at 1, 2, and 3 years. Patients with HFmrEF had significantly lower risk of cardiovascular (CV) deaths than HFrEF (RR = 0.77; 95% CI = 0.65–0.92; P < 0.001). Subgroup analysis showed that studies recruiting >50% of males had higher risk of deaths with HFrEF (RR = 1.15; 95% CI = 1.04–1.26; P = 0.006). When compared with HFpEF, patients with HFmrEF had comparable risk of all‐cause death (RR = 1.02; 95% CI = 0.96–1.09; P = 0.53). Similarly, there were no differences in the 1, 2, and 3 year deaths; CV and non‐CV deaths were insignificant between HFmrEF and HFpEF. Conclusions: The results of the study support that HFmrEF has better prognosis than HFrEF but similar prognosis when compared with HFpEF. Gender disparity between studies seems to influence the results between HFmrEF and HFrEF. Transition in left ventricular ejection fraction (LVEF), which could not be addressed in the study, may play a decisive role in determining outcomes. PROSPERO review registration number CRD42021277107.